How daily supervisor abuse and coworker support affect daily work engagement - Wang, Hongqing; Tang, Tianzhen (Frontiers in Psychology, 2022)
Using a daily diary approach, this paper explores the emotion mechanisms of daily abusive supervision and coworker support affect daily work engagement from the supervisor demand perspective and the coworker resource perspective. Based on a sample of 73 employees for 5 consecutive days in China. The results revealed that daily abusive supervision has a significant negative effect on daily work engagement, daily negative emotion mediated this relationship, and coworker support had a cross-level moderating effect between daily abusive supervision and daily negative emotion. We discuss the practical and theoretical implications of these findings.